Study of some physical fertility properties and introduce its maps of Altal and Mnein soils of Rural Damascus governorate. (Damascus University Journal of agriculture sciences, 2022)
This study was conducted to identify some physical fertility properties of northern part soils of Rural Damascus governorate (Altal, Mnein) and to introduce the physical fertility maps for the study area. (10) soils samples were collected at depth 0-30 cm and 30-60 cm, which rise about 885-1122 m above sea level ,and rainfall between 130-292 mm. Results indicated that the soils had a clayey texture (30.5) % in south Mnein to (60.5) % in the center of Maaraba. Specific gravity and Bulk density were at natural results, soils pH was (8.2), with no salinity (0.003) dS/m. The content of organic matter was high. Total porosity was good. Ossification ratio varied between (5) % in south west Mnein to (75) % in both north east Maaroneh and east Mnein.CaCO3 percentage was very high (more than 30) % except in the center of Maaraba. Fertility properties indicated that soils in Altal and Mnein were rich in total nitrogen (0.14 %), medium concentration with available phosphorus (8.5-12 ppm) and high concentration with available potassium (252-400 ppm).
Keywords: physical fertility properties; Altal; Mnein; Maaroneh; Maaraba; physical fertility maps